The dissertation journey during the COVID-19 pandemic: Crisis or opportunity?. (June 2022) - Opoku, Emmanuel K.; Chen, Li-Hsin; Permadi, Sam Y.
Abstract: Despite dissertation's significance in enhancing the quality of scholarly outputs in tourism and hospitality fields, insufficient research investigates the challenges and disruptions students experience amidst a public health crisis. This study aims to fill the research gaps and integrate attribution and self-efficacy theories to understand how the COVID-19 pandemic influences students' decision-making and behaviours during the dissertation writing process. Qualitative exploration with 15 graduate students was conducted. The results indicate that adjustment of data collection approaches was the most shared external challenge, while students' religious background and desire for publishing COVID related topics were primary internal motivations.